Methods principles construction of support and decision making systems for organisation collection and utilization organic raw materials - Komarchuk, D.; Shvorov, S.; Ohrimenko, P.; Chyrchenko, D. (Енергетика і автоматика, 2017)
Annotation. Analyzed ways to solve the national problems increase biomethane production through optimal planning seeding, harvesting and conversion into biogas energy crops and other organic waste. The proposed functional structure of support and adoption of decisions related to the collection and recycling of organic materials in order to obtain the maximum volume of biomethane.Keywords: biomethane, decision support system, organic materials, biogas, energy crops